The Formation of Physical Education Specialists’ Professional Training while late XIX - early XX centuries - Dyba., T. (Continuing Professional Education: Theory and Practice, 2023)
The author analyzed the formation of the national system of professional education. The preconditions of an international significance of physical education professional training were analyzed. The stage of physical education specialists’ vocational education that was before the October revolution was examined as an important phase in the development of vocational training in Ukraine. There was the contribution to solving the problem of physical education professional training of Lesgaft P., A. Butovo, I. Boberskyi, A. Anokhin analyzed, and their methods were aimed to the harmonious development of man and to solving the problem of physical education professional training. P.F.Lesgaft officially opened two-year long training and gymnastic courses; he proposed the principles of scientific validity of physical education based on the usage of following research methods: pedagogical, biomedical, psychological; he also developed the principles of professional training in physical education. O.D. Butovskii was the founder of the scientific system of military serviceman physical education; he was the first to substantiate theoretically the necessity of military serviceman obtaining not only common, but also specialized physical education. I. Boberskyi was the first to organize a training courses for morning work-out qualified teachers; he developed a sports terminology for morning work-out teachers; and he was for the first in Ukraine to organize women’s sports and gymnastic societies. O.K. Anokhin initiated and organized special courses for physical training teachers to improve their skills. The author notes that the described stage is very important in the development of professional training in Ukraine